Just queueing (JQ): Scheduling algorithm for the internet - Miaji, Yaser; Hassan, Suhaidi (IEEE Computer Society, 2009)
Fairness in packets scheduling in routers is a fundamental objective for designing a scheduler. The magnificent WFQ, which approximate GPS to a distinctive level of accuracy, attempts to allocate the bandwidth fairly among the flows according to Maxmin principle and to source-destination fashion. Nevertheless,referring to Rawls’ method for theory of justice, “rank alternatives to the worst possible outcome”, could be inferred as the distribution of the congestion, in case of its incidence, rather than the fairness. This article reveals the discussion in displacing scholars’ attention from bandwidth allocation to distribution of the congestion or the charge. It introduces the conceptual framework of just queuing (JQ) principle.